Cultural and Aesthetic Needs as Components of the Communicative Activity - Saetzyanovna Khakimzyanova, Alsu (2021)
The article considers the types of needs of the individual in the field of culture and art as a communicative component of modern society, namely, the cultural and aesthetic needs, which are based on the dissemination of social information. Social information in society is the most important condition for maintaining the activities of individual and collective entities at the level of modern requirements, goals and objectives of the individual. In the modern world, the interaction of cultures is the basis of social development and is of paramount importance, occupying a leading place in the value orientations of people. The information space creates a favorable field for the formation of personality, but also becomes an area of actual reality in which targeted influence and management of human interests, needs, beliefs and views are conducted. The basic needs of people in the field of culture and art can be considered as a way classification of their communicative activity. Developed cultural and aesthetic information needs absorb many of the highest human needs: in building a universal picture of the world and knowing those sides and phenomena that most interest a person in self-knowledge, self-education; in discussing the crucial issues of human being; in communication and self-expression in the development of their human forces and abilities.